The Implementation of Inquiry-Based Learning to Improve the Learning Result of Football - Saharullah, Saharullah; Idrus, Nur Abidah; Muhammadong, Muhammadong; Arisandy, Reski (Universitas Negeri Makassar, 2019)
The study aimed at improving students’ learning outcomes about football through the inquiry learning model at Vocational High School 2 Makassar. Data were collected using PJOK learning result test and observation. The results of recapitulation between cycles after implementing inquiry learning model indicate that football learning outcomes of students in grade X TKJ 1 at Vocational High School 2 Makassar improved, proven by the result in cycle I that 6 (17.1%) out of 35 students were in Moderate scale and only 1 student (2.9%) was in Poor scale. In cycle II, the learning outcomes improve as there were 10 students (28.6%) in Moderate scale. Classically, cycle I is stated as unsuccessful because only 74.29% of students were in the complete category and has not achieved successful indicators which had been determined. In cycle II, there was an improvement of completeness which was stated as successful because 91.43% of students were in the complete category and has not achieved successful indicator which had been determined, which was 80%. The inquiry learning model applied in teaching football can improve learning outcomes based on the achievement of learning results completeness classically and individually.